The Association Between Peri-Hemorrhagic Metabolites and Cerebral Hemodynamics in Comatose Patients With Spontaneous Intracerebral Hemorrhage: An International Multicenter Pilot Study Analysis - Rasulo, Frank; Piva, Simone; Park, Soojin; Oddo, Mauro; Megjhani, Murad; Cardim, Danilo; Matteotti, Ilaria; Gandolfi, Leonardo; Robba, Chiara; Taccone, Fabio Silvio; Latronico, Nicola (Frontiers in Neurology, 2020)
Background and Objective: Cerebral microdialysis (CMD) enables to monitor brain tissue metabolism and risk factors for secondary brain injury such as an imbalance of consumption, altered utilization and delivery of oxygen and glucose, frequently present following spontaneous intracerebral hemorrhage (SICH). The aim of this study is to evaluate the relationship between Lactate/Pyruvate ratio (LPR) with hemodynamic variables (mean arterial blood pressure [MABP], intracranial pressure [ICP], cerebral perfusion pressure [CPP], and cerebrovascular pressure reactivity [PRx]) and metabolic variables (glutamate, glucose and glycerol), within the cerebral peri-hemorrhagic region, with the hypothesis that there may be an association between these variables, leading to a worsening of outcomein comatose SICH patients. Methods: This is an international multicenter cohort study regarding a retrospective dataset analysis of non-consecutive comatose patients with supratentorial SICH undergoing invasive multimodality neuromonitoring admitted to Neuro Critical Care Units pertaining to three different centers. Patients with SICH were included if they had an indication for invasive ICP and CMD monitoring, were > 18 years of age and had a Glasgow Coma Scale (GCS) score of ≤ 8. Results: Twenty-two patients were included in the analysis; a total monitoring time of 1558 hours was analyzed, with a mean (SD) monitoring time of 70.72 hours (66.25) per patient. Moreover, 21 out of the 22 patients (95%) had disturbed cerebrovascular autoregulation during the observation period. When considering a dichotomized LPR for threshold levels of 25 or 40, there was a statistically significant difference in all the measured variables (PRx, Glucose, Glutamate) but not Glycerol. When dichotomized PRx was considered as the dependent variable, only LPR was related to autoregulation. Lower PRx was associated with higher survival [27.9% (23.1%) vs 56.0% (31.3%), p=0.03]. Conclusions: According to our results, disturbed autoregulation in comatose SICH patients is common, it is correlated to deranged metabolites within the peri-hemorrhagic region of the clot and it is also associated to poor outcome.